PENERAPAN THEORY OF PLANNED BEHAVIOR DALAM PEMBELIAN MAKANAN HALAL PADA MASYARAKAT DI KOTA BANDA ACEH - Luthfi Sagusta Putra, Ridwan Nurdin (Departemen Manajemen, 2018)
This study aims to examine intention to purchase halal food among community in the city of Banda Aceh by using Theory of Planned Behavior. This research uses 4 variable: intention to purchase halal food, attitude, subjective norm, and perceived behavior control. This research is a survey research using questionnaire as its instrument. The population used in this study is the community in the city of Banda Aceh. The sample in this study is 160 people who are Muslim and Non-Muslim communities in Banda Aceh City. Probability Sampling is used as a sampling technique with Cluster method. Based on the results of regression analysis showed that attitude, subjective norm, and perceived behavior control variables have positive and significant effect on intention to purchase halal foodKeywords: Theory of Planned Behavior, Muslim User, Halal Food